2019
DOI: 10.21608/zumj.2019.11284.1174
|View full text |Cite
|
Sign up to set email alerts
|

Potential Antiepileptic Effect of Ivabradine Against Pentylenetetrazole Induced- Kindleing in Male Mice

Abstract: Background: Ivabradine, Hyperpolarization activated cyclic nucleotide gated (HCN) channel blocker, is the most specific blocker of central nervous system Ih current. Valporate is one of the most commonly used antiepileptic drugs. Objectives: investigate the possible anticonvulsant effect of Ivabradine and its interaction with valporate in pentylenetetrazole (PTZ) induced-kindling in mice. Materials& Methods: mice were divided into four groups, "Group 1", "vehicletreated group" "Group 2", "PTZ kindling Control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…Likewise, IVN inhibits the expression of inflammatory signaling pathways, such as p38 mitogen activated protein kinase (p39MAPK), in rats with experimental DXR-induced cardiotoxicity (Zuo et al 2019 ). Furthermore, a recent study showed that IVN attenuates kindling in rats through its antioxidant effects (Ahmed et al 2020 ). Of note, exaggeration of inflammatory reactions and oxidative stress may induce the development of heart failure (Onohuean et al 2021 ; Teibo et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, IVN inhibits the expression of inflammatory signaling pathways, such as p38 mitogen activated protein kinase (p39MAPK), in rats with experimental DXR-induced cardiotoxicity (Zuo et al 2019 ). Furthermore, a recent study showed that IVN attenuates kindling in rats through its antioxidant effects (Ahmed et al 2020 ). Of note, exaggeration of inflammatory reactions and oxidative stress may induce the development of heart failure (Onohuean et al 2021 ; Teibo et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%